(untitled) (UNED Research Journal, 2016)
In Costa Rica, Patagioenas fasciata is distributed in forested areas of the highlands, from 900 m above sea level to the top of the ridges. We identified the main habitats of this species with thematic maps in GIS and did a geophysical analysis. The species is found in the highlands of Rincon de la Vieja, SanIgnacio de Acosta and San Vito de Coto Brus. Our information about possible migration routes, altitudes, weather elements and geomorphology of the sites where it moves and lives is relevant to the species’ management and conservation.